The Effect of Using The PBL (Problem Based Learning) Learning Model Assisted by ChatGPT on Student Learning Outcomes in The Reaction Rate Material - Sifa Nurul Aisyah; Mangara Sihaloho; Julhim S. Tangio; Astin Lukum; Haris Munandar; Thayban Thayban; Erga Kurniawati (Universitas Negeri Gorontalo, 2025)
Despite the importance of understanding reaction rate concepts in chemistry, students often struggle with abstract content and low engagement in traditional learning settings. Conventional teaching methods tend to emphasize rote memorization, limiting opportunities for critical thinking and problem-solving. This study investigated the influence of ChatGPT-assisted Problem-Based Learning (PBL) on students’ learning outcomes in reaction rate material. A quasi-experimental design with a non-equivalent control group was employed, involving two Class XI groups at SMA Negeri 1 Kabila: XI A as the experimental group (using ChatGPT-assisted PBL) and XI B as the control group (receiving conventional instruction). Learning outcomes were measured using an essay test aligned with cognitive indicators. Results showed greater improvement in the experimental group, with a posttest average of 78.68 compared to 69.23 in the control group. Independent sample t-test analysis revealed a significant difference between groups (p = 0.001 < 0.05), and the N-Gain score indicated a higher improvement category in the experimental class. These findings suggest that integrating ChatGPT into PBL enhances students’ understanding of reaction rate concepts and supports more effective learning, highlighting the potential of AI-assisted strategies in chemistry education.